Kerusakan Gigi pada Murid-Murid Dua Sekolah Dasar di Kecamatan Genteng dan Dua Sekolah Dasar di Kecamatan Semampir Surabaya - S. Djokowidodo (Faculty of Dentistry, Universitas Indonesia, 2015)
The objective of this research was to find out whether a difference in social economic background causing different in dental impairment among two group of elementary school children. Using mouth mirror, sonde and observing the two group of elementary school children : 1. From Subdistrict of Genteng, whose parents are able to provide moderm food (814 children). 2. From Subdistrict of Semampir, whose parent are relatively unable to provide moderm food (936 children). Analyzing with T test, it was found that caries indexes (DMF and def) in both groups showed no significant difference.